Immunohistochemical and Clinicopathologic Profiling of Pituitary Adenomas at a Nigerian Tertiary Hospital - Uchime KE; Ajayi OO; Awolola NA; Bankole OB; Anunobi CC (Annals of Health Research, 2024)
Background: Pituitary adenoma is the most common pituitary tumour and the third most common intracranial tumour worldwide. Only a few studies have been done in Africa on the immunohistochemical expression pattern and clinicopathologic presentations of the different hormonal subtypes of pituitary adenomas.